Sustainability reporting and audit committee attributes: Evidence from banks in Indonesia - Inten Meutia; Zulnaidi Yaacob; Shelly F. Kartasari (Asian Academy of Management Journal, 2023)
This paper examined the effects of audit committee attributes on the sustainability reporting (SR) of commercial banks in Indonesia. This study conducted a cross-sectional and time-series analysis using a sample of 74 commercial banks from 2015 to 2019. This study investigated the audit committee attributes, including financial expertise, size, independence, and meeting frequency. The model under study was underpinned by the theory of legitimacy, stakeholders, and agency. The results showed that the financial expertise of audit committee had an inverse relationship with SR disclosure. Meanwhile, there was a positive relationship between committee independence, bank size, bank age, and type of auditor with SR disclosure. These findings imply that the banks should further focus on the audit committee’s attributes as an effective measure to produce quality SR disclosure. In addition, non-financial expertise, especially in the field of sustainability, is a skill that the audit committee needs to have.